Implementation of Laplace Transformed MP2 for Periodic Systems With Numerical Atomic Orbitals - Shang, Honghui; Yang, Jinlong (Frontiers in Chemistry, 2020)
We present an implementation of the canonical and Laplace transformed formulation of the second-order Møller–Plesset perturbation theory under periodic boundary conditions using numerical atomic orbitals. To validate our approach, we show that our results of the Laplace transformed MP2 correction for the total energy and the band gap are in excellent agreement with the results of the canonical MP2 formulation. We have calculated the binding-energy curve for the stacked trans-polyacetylene at the Hartree-Fock+MP2 level as a preliminary application.